Endothelial-to-mesenchymal transition: a precursor to pulmonary arterial remodelling in patients with idiopathic pulmonary fibrosis. Issue 2 (17th April 2023) - Gaikwad, Archana Vijay; Lu, Wenying; Dey, Surajit; Bhattarai, Prem; Haug, Greg; Larby, Josie; Chia, Collin; Jaffar, Jade; Westall, Glen; Singhera, Gurpreet Kaur; Hackett, Tillie-Louise; Eapen, Mathew Suji; et al.
Background: We have previously reported arterial remodelling in patients with idiopathic pulmonary fibrosis (IPF) and suggested that endothelial-to-mesenchymal transition (EndMT) might be central to these changes. This study aims to provide evidence for active EndMT in IPF patients. Methods: Lung resections from 13 patients with IPF and 15 normal controls (NCs) were immunostained for EndMT biomarkers: vascular endothelial cadherin (VE-cadherin), neural cadherin (N-cadherin), S100A4 and vimentin. Pulmonary arteries were analysed for EndMT markers by using computer- and microscope-assisted image analysis software Image ProPlus7.0. All the analysis was done with observer blinded to subject and diagnosis. Results: Increased expression of mesenchymal markers N-cadherin (p<0.0001), vimentin (p<0.0001) and S100A4 (p<0.05) was noted with downregulation of junctional endothelial VE-cadherin (p<0.01) in the intimal layer of the arteries from patients with IPF compared to NCs. Cadherin switch was observed in IPF patients, showing increase in endothelial N-cadherin and decrease in VE-cadherin (p<0.01). There was also VE-cadherin shift from junctions to cytoplasm (p<0.01), effecting endothelial cell integrity in patients with IPF. In IPF, individual mesenchymal markers vimentin and N-cadherin negatively correlated with diffusing capacity of the lungs for carbon monoxide (r′= −0.63, p=0.03 and r′= −0.66, p=0.01). Further, N-cadherin positively correlated with arterial thickness (r′=0.58, p=0.03). Conclusion: This is the first study to demonstrate active EndMT in size-based classified pulmonary arteries from IPF patients and potential role in driving remodelling changes. The mesenchymal markers had a negative impact on the diffusing capacity of the lungs for carbon monoxide. This work also informs early origins of pulmonary hypertension in patients with IPF. EndMT is an active process in patients with IPF, and contributes to pulmonary arterial remodelling and fibrosis. This work also informs the early origins of pulmonary hypertension in patients with IPF. EndMT is a novel therapeutic target in IPF. https://bit.ly/3Hof1pZ